2014
DOI: 10.1007/s10681-014-1230-1
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis for yield and drought tolerance traits under managed drought stress in sweetpotato

Abstract: Drought is among sweetpotato production constraints in sub-Saharan Africa. Two studies were conducted on 15 F 1 sweetpotato families (G1-G15) generated using a half-diallel mating scheme of six parents. The first experiment was conducted at Kenya Agricultural Research Institute (KARI), Kiboko, using split plot design under drought stress and no drought stress replicated twice and repeated thrice between January 2012 and June 2013. The second study was conducted in the screen house at KARI, Muguga using randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 14 publications
1
19
1
1
Order By: Relevance
“…Variable DMC has been reported in Kenya ranging from 23.5 to 34.5% (Kivuva et al, 2015). According to the 2014 catalog of Orange-Fleshed Sweetpotato for Africa, the orange fleshed sweetpoaoto genotypes KENSPOT-3 and KENSPOT-5 had DMC of 32.5% and 25.9%, in that order.…”
Section: Discussionmentioning
confidence: 99%
“…Variable DMC has been reported in Kenya ranging from 23.5 to 34.5% (Kivuva et al, 2015). According to the 2014 catalog of Orange-Fleshed Sweetpotato for Africa, the orange fleshed sweetpoaoto genotypes KENSPOT-3 and KENSPOT-5 had DMC of 32.5% and 25.9%, in that order.…”
Section: Discussionmentioning
confidence: 99%
“…The GCA effect is the average performance of a certain parent over a series of hybrids, and it is associated with additive gene effects, whereas the SCA effect reveals deviations in the performance of a certain cross from the performance predicted by the parents' GCA effects, and it is associated with nonadditive gene effects (Musembi et al 2015). In the current study, the GCA to SCA variance ratios of the MFVW were approximately equal to 1 and the narrow sense heritability of the MFVW was approximately 51.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Kivuva et al (2015), Balcha (2015), and Rukundo et al (2017) reported that the positive and significant GCA effects in agronomic traits indicate the presence of additive gene action and parents with these genetic characters could be considered as good combiners in a hybridization program. In this study, clone Tio-Joe had positive and significant GCA effects for number of storage roots, harvest index and beta carotene content, while clone Ininda had positive GCA effect for fresh root yield and dry matter content only (Table 6).…”
Section: General and Specific Combining Ability Effectsmentioning
confidence: 99%